1996
DOI: 10.1163/2211730x96x00180
|View full text |Cite
|
Sign up to set email alerts
|

Elza Kriuger

Abstract: Perfusion of the isolated rabbit heart with 5 x 10(6) human polymorphonuclear leukocytes, under recirculating conditions (50 ml), and challenge with A-23187 (0.5 microM) caused an increase in coronary perfusion pressure (from a prechallenge value of 46 +/- 1.1 to 176.2 +/- 29.7 mm Hg, 30 min after challenge, n = 6-4), which was linearly correlated (P < .006) with formation of cysteinyl leukotrienes (29.7 +/- 7.3 pmol/ml, 30 min after challenge). Pretreatment with the leukotriene synthesis inhibitor BAY X1005 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It is important to note that in the same in vivo experimental model, pretreatment with the 5-lipoxygenase activating protein inhibitor, BAY X1005, caused significant cardioprotection and reduced mortality. This suggests that inhibition of LTA 4 biosynthesis and, ultimately, of transcellular biosynthesis to the cysteinyl leukotrienes played a significant role in the cardiac events [36]. Indeed, the elevation of urinary LTE 4 had been reported previously in human subjects with acute myocardial infarctions or unstable angina [7], as well as in human subjects with atherosclerotic coronary artery disease prior to bypass surgery [1].…”
Section: In Vivo Modelsmentioning
confidence: 86%
“…It is important to note that in the same in vivo experimental model, pretreatment with the 5-lipoxygenase activating protein inhibitor, BAY X1005, caused significant cardioprotection and reduced mortality. This suggests that inhibition of LTA 4 biosynthesis and, ultimately, of transcellular biosynthesis to the cysteinyl leukotrienes played a significant role in the cardiac events [36]. Indeed, the elevation of urinary LTE 4 had been reported previously in human subjects with acute myocardial infarctions or unstable angina [7], as well as in human subjects with atherosclerotic coronary artery disease prior to bypass surgery [1].…”
Section: In Vivo Modelsmentioning
confidence: 86%
“…MK-886 prevented the biochemical changes and protected the lung morphology after HS. Although leukotrieneshave been known to be associated with the I/R injury in other tissues, including intestine [24] kidney [25], myocardium [26] and liver [27], there are only a few studies describing the correlation between hemorrhagic shock-induced lung injury and 5-lipoxygenase pathway products, where two studies demonstrated that the 5-lipoxygenase pathway products meditate acute lung injury following hemorrhagic shock [28,29]. And it has been demonstrated that LTB4 levels were significantly increased in the rat lungs following T/HS [30].…”
Section: Discussionmentioning
confidence: 99%